Strategi Komunikasi Pemasaran dalam Meningkatkan Brand Awareness melalui Media Sosial Instagram @molla_studio - Hanif Muhtarom Ayoga; Edy Purwo Saputro (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Competition between business actors has increased significantly, so that in maintaining a brand, service or goods sellers require an appropriate and effective marketing strategy. Instagram is one of the social media that can be used for marketing communication media. The purpose of this study is to determine the marketing communication strategy used by Molla Studio to increase brand awareness through Instagram social media. This study was conducted using a qualitative descriptive method from March to May 2025. The sampling technique used was purposive sampling. Data was obtained through interviews with four sources (owners, Instagram account managers, and two consumers), observation, and documentation. The results of the study showed that the marketing communication strategy used by Molla Studio by utilizing Instagram social media with the STP approach (Segmenting, Targeting, and Positioning) and using the 7P Marketing Mix strategy (Product, Promotion, Price, Place, People, Process, and Physical Evidence). The use of this strategy has been proven to increase brand awareness and increase the number of consumers.